(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The number of orbital bristles and the presence of the first cross-vein at 2/3 of discal cell in the wing which have been noticed in numerous specimens of Amauromyza morionella collected on Ballata sp., lead to a new consideration and description of subspecies novaki (Strobl).